Interactive Internet artistry. - Stein, M.R.
The paper describes painting on the World Wide Web with the PumaPaint project. The project is a web site allowing any user with a Java-compatible web browser to control a PUMA 760 robot. The site allows users to perform the single task of painting on an easel with real brushes and paint. We see the contribution of the project deriving mainly from the chosen task of painting. Rather than providing the user a general ability to move and observe a robot, our interface is focused on a specific task. The interface provides the opportunity to achieve remarkable subtlety, greatly affecting the resulting visual impression. The real interest in the project for the authors, and the motivation for developing it, is the artwork produced
Keywords: Internet; PUMA 760 robot; PumaPaint project; World Wide Web; Artistry; Interactive system; Robotic painting; Telerobotics; User interface